1995
DOI: 10.1080/10862969509547889
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Instruction during Reading Lessons in six Classrooms

Abstract: This study was conducted to explore two research questions: (a) How do teachers teach meaning vocabulary during reading lessons? and (b) What are teachers' stated purposes for teaching meaning vocabulary? The data were collected in six classrooms, three each at the fifth-and sixth-grade levels, in a large urban school district. Reading instruction in each of the six classrooms was observed over the course of 4 months, for a total of 47 observations. At the end of the observation period, participating teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 22 publications
5
46
0
2
Order By: Relevance
“…Consistent with previous research that has documented, for several decades, the limited time spent on vocabulary instruction in many classrooms (e.g., Durkin, 1978Durkin, /1979Roser & Juel, 1982;Scott, Jamieson-Noel, & Asselin, 2003;Watts, 1995), informal observations at the three schools studied revealed that none of them emphasized language instruction in general or attention to morphology in particular. Had there been a specific instructional focus on these elements of language, these learners may have developed more sophisticated morphological awareness and broader vocabulary knowledge sooner, which would have likely accelerated the development of reading comprehension ability.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with previous research that has documented, for several decades, the limited time spent on vocabulary instruction in many classrooms (e.g., Durkin, 1978Durkin, /1979Roser & Juel, 1982;Scott, Jamieson-Noel, & Asselin, 2003;Watts, 1995), informal observations at the three schools studied revealed that none of them emphasized language instruction in general or attention to morphology in particular. Had there been a specific instructional focus on these elements of language, these learners may have developed more sophisticated morphological awareness and broader vocabulary knowledge sooner, which would have likely accelerated the development of reading comprehension ability.…”
Section: Discussionsupporting
confidence: 87%
“…A second important contribution to the literature is that this study looked at K-3 teachers. Most other studies examined vocabulary instruction at the fourth-grade and beyond (Blachowicz, 1987;Blanton & Moorman, 1990;Durkin, 1978Durkin, -1979Scott et al, 2003;Watts, 1995). This study focus on K-3 classroom teachers reveals that teachers were not, as often assumed, teaching vocabulary simply as part of sight word or decoding instruction but were introducing new word meanings.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, the percentages of time that she observed this type of vocabulary instruction were between 6.75% and 11%. Watts (1995) conducted the most detailed observational study of vocabulary instruction to date. She worked in six classrooms, three each at the fifth and sixth grade.…”
Section: Classroom Vocabulary Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pesar de la importancia del conocimiento del vocabulario para el desarrollo de la lectoescritura, la enseñanza sistemática de vocabulario en las escuelas primarias sigue siendo extremadamente rara (Scott, Jamielson-Noel y Asselin 2003;Watts 1995). El énfasis de las escuelas en las habilidades de lectura (identificación de palabras) durante los primeros años de instrucción generalmente no requiere conocimientos de vocabulario demasiado avanzado (Becker 1977;Biemiller 2001).…”
Section: Enseñanza Efectiva Del Vocabulariounclassified